Heck and oxidative boron Heck reactions employing Pd(II) supported amphiphilized polyethyleneimine‐functionalized MCM‐41 (MCM‐41@aPEI‐Pd) as an efficient and recyclable nanocatalyst. (16th October 2017) - Motevalizadeh, Seyed Farshad; Alipour, Masoumeh; Ashori, Fatemeh; Samzadeh‐Kermani, Alireza; Hamadi, Hosein; Ganjali, Mohammad Reza; Aghahosseini, Hamideh; Ramazani, Ali; Khoobi, Mehdi; Gholibegloo, Elham
Abstract : A novel nanocatalyst was developed based on covalent surface functionalization of MCM‐41 with polyethyleneimine (PEI) using [3‐(2, 3‐Epoxypropoxy)propyl] trimethoxysilane (EPO) as a cross‐linker. Amine functional groups on the surface of MCM‐41 were then conjugated with iodododecane to render an amphiphilic property to the catalyst. Palladium (II) was finally immobilized onto the MCM‐41@PEI‐dodecane and the resulted MCM‐41@aPEI‐Pd nanocatalyst was characterized by FT‐IR, TEM, ICP‐AES and XPS. Our designed nanocatalyst with a distinguished core‐shell structure and Pd 2+ ions as catalytic centers was explored as an efficient and recyclable catalyst for Heck and oxidative boron Heck coupling reactions. In Heck coupling reaction, the catalytic activity of MCM‐41@aPEI‐Pd in the presence of triethylamine as base led to very high yields and selectivity. Meanwhile, the MCM‐41@aPEI‐Pd as the first semi‐heterogeneous palladium catalyst was examined in the C‐4 regioselective arylation of coumarin via the direct C‐H activation and the moderate to excellent yields were obtained toward different functional groups. Leaching test indicated the high stability of palladium on the surface of MCM‐41@aPEI‐Pd as it could be recycled for several runs without significant loss of its catalytic activity. Abstract : Functionalizing the surfaces of MCM‐41 with polyethylenimine (PEI) and [3‐(2, 3‐epoxypropoxy)propyl]trimethoxysilane (EPO) and its amphiphilization by Iodododecane conjugation, then the adsorption of Pd inside its shell to produce MCM‐41@aPEI‐Pd, as an efficient, selective and stable nanocatalyst for the Heck and oxidative boron Heck reactions.